HUBUNGAN UMUR DAN PARITAS IBU TERHADAPKEJADIAN BAYI BBLR DI RSU DR.WAHIDINSUDIRO HUSODO KOTA MOJOKERTO - Dewi Yanti, Ariu; Mukoyaroh, Nurul (JURNAL KEPERAWATAN SEHAT, 2015)
Low birth weight babies (LBW) is a newborn whose weight at birth of less than 2500 grams to 2499 grams. Class of low birth weight can be classified into two, the first is the pure prematurity of babies born with gestation <37 weeks and birth weight in accordance with the so-called gestation or preterm neonates according to her pregnancy, the baby is small gestastional age (SGA) is the weight of the baby born incompatible with pregnancy. This study aims to determine the correlation between age and maternal parity on the incidence of Low Birth Weight Babies (LBW) in RSU dr. Wahidin Sudiro Husodo Mojokerto. This research design use analytic retropektif with cross sectional approach. The population in this study were all mothers who gave birth to babies with low birth weight and her baby as many as 52 babies LBW. Samples were taken by total sampling. Instruments in this research is observation sheet then analyzed using cross tabulation. The results showed that there is correlation between age and maternal parity on the incidence of low birth weight babies in RSU dr. Wahidin Sudiro Husodo Mojokerto proven with results of 100% at age <20 years and 96.4% in primiparous mothers. Mothers age and parity may affect the babys birth. The younger the age of childbirth risk of having a baby of low birth weight, and the older the age of giving birth are also at risk of having a baby of low birth weight. Mother with first parity times the risk of having a baby of low birth weight, the higher the mothers parity the more at risk for having a baby of low birth Weights.Keywords: Age, Parity, Low Birth WeightAriuDewi Yanti